If you don't play, you're out! : Practices, strategies and interests: an analysis of the editorial-scientific game in Management (Management and Connections Journal, 2023)
The editorial-scientific field is a space for interaction and academic debate constituted by artifacts for the dissemination of knowledge. In this article, we sought to understand the Brazilian field of Administration as a space of dispute that manifests itself through the power relations that involve editorial practice. Pierre Bourdieu's theory was used as an approach, in which we consider the habitus, the rules of the game, the editor's position, capital and disputes for recognition. For this, eleven editors of scientific journals in the area were interviewed. The theoretical corpus was analyzed using Thematic Analysis, thus building an image of the editors' experiences. It is understood that editors play the editorial game with practices and strategies that are not publicly legitimized. It is considered that the main purposes are personal recognition based on the elevation of the journal for which they are responsible. Aspects were found that reveal power games and that connect with the search for symbolic capital.
Keywords: Academic-scientific field; Symbolic Power; Scientific Authorithy; Administration